HUBUNGAN PERILAKU PENGGUNAAN INSEKTISIDA, PERILAKU 3M, DAN KEBERADAAN BREEDING PLACE DENGAN KEJADIAN DBD DI KOTA SEMARANG (STUDI PADA USIA 12-25 TAHUN) - Hepi Prihati Hayu Laturohmi; Nur Endah Wahyuningsih; Retno Murwani (Jurnal Kesehatan Masyarakat (Undip), 2016)
Semarang City is an area endemic with the number of patients in 2014 amounted to 1,628 people. CFR of DBD in Semarang is 1.14% in 2013 and rose to 1.66% in 2014. IR of DBD in Semarang first ranked than IR DBD in Central Java, 92.43. This study aims to identify factors associated with the incidence of DHF in Semarang. This study is a case control study that used a retrospective approach. The population in this study are patients with DHF in dr. Kariadi Hospital, Tugurejo Hospital, SMC Telogorejo, and Ketileng Hospital. Samples are adolescents aged 12-25 years. Data were analyzed using Chi Square test with a confidence level of 95% or 5% significance level. The results showed that the practice to use of insecticide obtained p value 0.321 (OR = 1.643; CI = 0.614 to 4.396). Practice 3M obtained p value of 0.103 (OR = 2.156; CI = 0.851 to 5.464). The existence of breeding place obtained p value of 0.806 (OR = 0.886; CI = 0.338 to 2.324). From these results we conclude that the behavior of the use of insecticides, 3M behavior, and the presence of breeding place showed no relationship with the dengue incidence in Semarang.